Microbial complexity at peri-implantitis versus periodontitis sites - William Bane, DMD (Elsevier, 2024)
OBJECTIVES: The purpose of this investigation was to compare the diversity of microbial communities at peri-implantitisversus stage III/IV periodontitis-affected sites using next-generation sequencing. METHODS: Seven subgingival plaque specimens from each group of human donors diagnosed with peri-implantitis, stage III/IV periodontitis, or clinical gingival health (control group) were collected. Bacterial DNA was extracted, and the V4 region of the 16s rRNA gene was amplified. PCR-generated amplicons were sequenced, and operational taxonomic units (OTUs) were classified using the Silva database. Shannon Diversity Indices (SDIs) were estimated, and alpha diversity differences were tested using ANOVA. Bray-Curtis indices were computed to estimate beta diversity across groups, and Principal Coordinate Analysis (PCoA) ordination was completed. Significant variations in microbiome structure across groups was assessed using PERMANOVA. Genera that were differentially abundant across groups (absolute log2 fold change > 2) were identified. RESULTS: OTUs clustered into three distinct groups based on sample source. PCoA results demonstrated statistically significant differences between clinical health and peri-implantitis (P-adjusted < 0.05), between clinical health and periodontitis (P-adjusted < 0.05), and between peri-implantitis and periodontitis (P-adjusted < 0.05). Biofilms derived from cases of clinical health exhibited a mean SDI of 2.46. By comparison, mean SDIs in the peri-implantitis and periodontitis groups amounted to 3.023 (Padjusted < 0.05) and 3.061 (P-adjusted < 0.05), respectively. Between the peri-implantitis and periodontitis groups, 8 OTUs exhibited statistically significant differential abundance. The genera Streptobacillus and Psychrobacter were dominant in the peri-implantitis group. CONCLUSIONS: Microbial differences between the diseased environments could not be attributed to the unequivocal presence or absence of specific bacteria. Nonetheless, statistically significant differences in biofilm composition and complexity could be identified between peri-implantitis and stage III/IV periodontitis specimens. IMPLICATIONS: An emerging hypothesis in periodontology and dental implantology posits that inflammatory destruction of tissue results not from the presence of one or a few key bacterial species. Rather, disease results from true polymicrobial activity characterized by accumulation of specific genes, and thus functions, within the biofilm. Moreover, the pathogenesis of peri-implantitis is known to involve the presence of titanium particles that influence the inflammatory response. The observed differences in biofilm diversity and composition in this investigation may reflect complex interactions involving titanium particles, host immune cells, and the biofilm at peri-implantitis sites.